Peran Lembaga Kejaksaan, Polri dan PPATK dalam Perampasan Aset Tindak Pidana Pencucian Uang (TPPU) Lintas Negara (Studi Kasus Putusan Kasasi No. 4950 K/Pid.Sus/2023) : Penelitian - Fajar, Rizki (Lembaga Penelitian dan Pengabdian Masyarakat, 2026)
This study examines the cross-border ML asset confiscation regulations related to the assets of defendants/convicts in Singapore and Australia, as well as the Supreme Court Justice's considerations in Cassation Decision No. 4950 K/Pid.Sus/2023. Legal materials were collected through document studies, presented systematically, analyzed qualitatively and juridically, and concluded deductively. The results of the study indicate that although cross-border ML asset confiscation regulations continue to evolve, the asset confiscation mechanism still requires regulations that explicitly regulate the types of assets that can be confiscated, the processes and procedures, as well as arrangements for cooperation, profit sharing, and reimbursement with other countries, particularly Singapore and Australia. The government requires strong political will and strengthened bilateral and multilateral cooperation in the tracing, blocking, seizure, and confiscation of assets. Furthermore, the Supreme Court Justice's considerations in the decision, particularly regarding imprisonment, fines, and compensation, are deemed to have not met the sense of justice because assets abroad cannot necessarily be effectively confiscated as a source of payment for state losses.